ФОНОСЕМАНТИЧЕСКАЯ КАРТИНА МИРА: К ПОСТАНОВКЕ ПРОБЛЕМЫ (Philological Studies, 2019)
In the paper defines the concept Sound Iconism picture of the world (Phono-semantic World Picture). Phono-semantic World Picture is part of the Language World Picture, which is explicated in the language using Phono-semantic means (Phono-semantic clusters). Various Phono-semantic clusters (onomatopoeia, sound symbolic words, initial and final phonesthemes and other) are the basis imaging sound-iconicity system of the language, which is the basis Phono-semantic World Picture. Universality and specificity phono-semantic picture of the world are considered on the level of onomatopeia German and Russian language and Russian dialects. It is shown that different phono-semantic clusters (reduplication, phonestheme, initial) different languages (old English, French, Arabic, English, German, Abaza, Chechen, Greek, Slavonic languages) are carriers of a common semantic space. It is established that Phono-semantic pictures of the world any languages of the world will have more similarities than different. The analysis shows that phono-semantic picture of the world has the same properties as the language picture of the world. It is a way of conceptualizing the world. It has properties of consistency, specificity, integrity, variability, cosmology and anthropomorphism, and also unity of stability and variability, universal and national features. These traits have a language picture of the world. The result concludes that phono-semantic picture of the world as a fragment of the language picture of the world can only be viewed in the context of traditional linguistics. Phono-semantic World Picture is not a fragment of the language picture of the world, it is its core, protoconceptual basis, primary element.Many researchers witness about the leading role of iconicity principle (at the level of different phono-semantic clusters) in the development and functioning of language. The thesis of genetic priority of iconic (onomatopoeic and sound symbolic) phono-semantic clusters in the origin and evolution of languages is hypothetically argued.
Keywords: Sound Iconism picture of the world, phono-semantics, iconicity, onomatopoeia, German, Russian, Russian dialects, Slavonic languages